Attenuation effect of Moringa oleifera leaves powder on Blood Biochemical disturbance induced in lead-exposed rats - AKPOVI, DEWANOU CASIMIR; SEGBO, JULIEN A. GAÉTAN; SENOU, MAXIMIN; ANAGO, AHOÉFA AMÉLÉ EUGÉNIE (My University, 2016)
The nutritional and phytopharmaceutical composition of Moringa oleifera leaves suggest that this vegetable can prevent toxic effects induced by xenobiotics .The current study aims to assess the prophylaxic capacity of Moringa oleifera leaves powder (MoLP) on biochemical disturbances in lead-exposed rats. Twenty-eight (28) Wistar rats were equally divided into four groups receiving respectively distilled water (Control), MoLP, lead acetate andboth lead acetate + MoLP. The treatment was administrated orally for 28 days. Blood samples were collected from animals at day zero (D0) and D28 for biochemical assays. Results showed that lead treatment decreased significantly the levels of total proteinemia (p<0.01), albuminemia (p<0.05), serum iron (p<0.01) and calcemia (p<0.01) compared to control group. MoLP addition to lead treatment produced opposite effect on these parameter levels and reversed the impact of lead treatment. The levels of blood urea (p<0.001), creatinine (p<0.01) and uric acid (p<0.01) increase significantly in lead-treated animals compared to controls. MoLP treatment induced no significant difference in the levels of blood urea, creatinine and uric acid. However, it suppresses the effect of lead treatment. On the whole, these results showed that MoLP administration to rats reverses lead deleterious effects on many circulating biochemical parameters. The results highlight MoLP importance in the attenuation of some biochemical disturbances associated with chronic lead absorption and strengthen arguments in favour of the use of MoLP as food supplement.
Keywords: Lead toxicity; Moringa oleifera leaves powder; Biochemical disturbances; Blood; Rat